2009
DOI: 10.1088/0004-637x/701/2/1436
|View full text |Cite
|
Sign up to set email alerts
|

Gj 3236: A New Bright, Very Low Mass Eclipsing Binary System Discovered by the Mearth Observatory

Abstract: We report the detection of eclipses in GJ 3236, a bright (I = 11.6), very low mass binary system with an orbital period of 0.77 days. Analysis of light and radial velocity curves of the system yielded component masses of 0.38 ± 0.02 M and 0.28 ± 0.02 M . The central values for the stellar radii are larger than the theoretical models predict for these masses, in agreement with the results for existing eclipsing binaries, although the present 5% observational uncertainties limit the significance of the larger ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 56 publications
2
54
1
Order By: Relevance
“…Toward this goal, we encourage other researchers to publish Hα measurements for their targets, as this is usually readily available from the spectra used to determine radial velocities. Indeed, a number of low-mass EBs with accurate masses and radii have been published in the last few years (e.g., Vaccaro et al 2007;Irwin et al 2009Irwin et al , 2011Morales et al 2010;Kraus et al 2011;, potentially increasing by a factor of 2-3 the small sample that we have used from López- Morales (2007). We are currently collecting new Hα measurements for these published EBs that lack resolved Hα measurements in order to improve the empirical relations that we have presented here.…”
Section: Discussionmentioning
confidence: 98%
“…Toward this goal, we encourage other researchers to publish Hα measurements for their targets, as this is usually readily available from the spectra used to determine radial velocities. Indeed, a number of low-mass EBs with accurate masses and radii have been published in the last few years (e.g., Vaccaro et al 2007;Irwin et al 2009Irwin et al , 2011Morales et al 2010;Kraus et al 2011;, potentially increasing by a factor of 2-3 the small sample that we have used from López- Morales (2007). We are currently collecting new Hα measurements for these published EBs that lack resolved Hα measurements in order to improve the empirical relations that we have presented here.…”
Section: Discussionmentioning
confidence: 98%
“…The findings presented herein are the result of more than 15 years of high-precision Doppler monitoring of nearby stars. Additional information will soon pour in from other surveys using techniques such as microlensing (e.g., Dong et al 2009;Gould et al 2010), astrometry (Boss et al 2009), transits (Borucki et al 2004;Barge et al 2008;Irwin et al 2009), and direct imaging (Claudi et al 2006;Artigau et al 2008;Macintosh et al 2008).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In that work, we found that all period-phased MEarth candidates above a transit depth signal to noise of D/σ MarPLE > 7.5 were either catastrophic instrumental problems, obvious stellar variability artifacts, or bona fide eclipsing systems Irwin et al 2009Irwin et al , 2010Irwin et al , 2011b. GJ1214b was identified in 2009 before the development of the full MISS MarPLE framework, using the box-fitting least squares search algorithm (Kovács et al 2002) and pre-cleaning with an iterative median filter (Aigrain & Irwin 2004) and trend filtering algorithm (Kovács et al 2005).…”
Section: Transit Detection Efficienciesmentioning
confidence: 99%